Pirfenidone in Idiopathic Pulmonary Fibrosis: Real-World Observation on Efficacy and Safety, Focus on Patients Undergoing Antithrombotic and Anticoagulant - Nicolò Reccardini; Maria Chernovsky; Francesco Salton; Paola Confalonieri; Lucrezia Mondini; Mariangela Barbieri; Antonio Romallo; Marta Maggisano; Chiara Torregiani; Pietro Geri; Michael Hughes; Corrado Campochiaro; et al. (MDPI AG, 2024)
Idiopathic pulmonary fibrosis (IPF) is a rare and progressive interstitial lung disease characterized by irreversible distortion of lung architecture and subsequent loss of pulmonary function. Pirfenidone is an antifibrotic agent associated with increased progression-free survival and overall survival rates, but it carries multiple side effects. The aim of the study was to examine the efficacy and safety profile of pirfenidone in a real-life context, with a focus on the concomitant use of antithrombotic and/or anticoagulant treatments. The clinical and functional data (forced vital capacity [FVC], forced expiratory volume in 1 s [FEV1], diffusing lung capacity for carbon monoxide [DLCO], and 6 min walking test distance [6MWD]) of all IPF patients treated with pirfenidone and referred to our two centers between 2019 and 2022 were retrospectively analyzed at baseline, 6 and 12 months after the start of treatment. A total of 55 IPF subjects undergoing pirfenidone treatment were included in the analysis (45.5% females, median [IQR] age at disease onset 68.0 [10.0] years, median [IQR] age at baseline 69.0 [10.8] years). Compared to baseline, at 12 months, FVC (86.0% vs. 80.0%; p = 0.023) and DLCO (44.0% vs. 40.0%; p = 0.002) were significantly reduced, while FEV1 (p = 0.304) and 6MWD (p = 0.276) remained stable; no significant change was recorded at 6 months. Most of the reported adverse events were mild or moderate. Gastrointestinal intolerance (9.1%) was the main cause of treatment discontinuation. A total of 5% of patients reported at least one minor bleeding event, although all episodes occurred in those receiving concomitant antithrombotic or anticoagulant. Overall, this real-life experience confirms the efficacy and safety profile of pirfenidone in the case of the concomitant use of antithrombotic and/or anticoagulant drugs.